Application of Dempster Shafer to Diagnose Cholecystitis Based on Web - Selviyani, Selviyani; Budi Serasi Ginting; Yani Maulita (CV. AFDIFAL MAJU BERKAH, 2024)
Cholecystitis is an inflammation of the gallbladder. The gallbladder is an organ where bile is stored, which is a fluid that plays an important role in the digestion of fat in the body. Data processing at Bangkatan Hospitals is currently still done by means of patients coming to the hospital and heading to the receptionist to carry out the process before meeting an expert (doctor), it makes patients have to queue and wait their turn to meet the doctor. The current lack of knowledge and information from the community/patients causes delays in handling the early symptoms of cholecystitis. This makes this research carried out by building an expert system that is able to diagnose cholecystitis. With the dempster shafer method, it is expected to be able to provide a high level of accuracy. From the calculation process using the Dempster Shafer method, it can be concluded that the disease suffered by the user is Acute Cholecystitis with a density value of 0.571 or 57.1%.